Cultural Riches: An Analysis of BIPA Materials at Andalas University - Nurilah, Indah; Tiawati, Refa Lina; Rahmat, Wahyudi (Journal of Humanity Studies, 2023)
This research is motivated by the cultural elements contained in the BIPA teaching materials at Andalas University. The method used in this research is content analysis. The data used is data obtained from cultural material contained in BIPA teaching materials at Andalas University. Data collection techniques use reading and note-taking techniques. The data sources in this research are six BIPA teaching materials including Indonesian language textbooks for foreign speakers (BIPA) at the basic level, Indonesian language textbooks for foreign speakers (BIPA) at the advanced basic level, Indonesian grammar for foreign speakers at the basic level, writing. Indonesian for basic level foreign speakers, listening Indonesian for basic level foreign speakers, speaking Indonesian for basic level foreign speakers from Andalas University. According to the results of the analysis, 2 vocal and language symbol systems were found, a knowledge system, a social organization system, a living equipment and technology system, a livelihood system, a religious and artistic system.